Faktor-Faktor Yang Mempengaruhi Struktur Modal Sektor Industri Barang Konsumsi Sub Sektor Makanan Dan Minuman Yang Terdaftar Di Bursa Efek Indonesia Periode 2018-2021 - Hani Krisnawati; Y. Sutomo; Mudjiyono Mudjiyono; Risma Martha Sella (Jurnal Riset Akuntansi, 2023)
This study aims to determine the effect of profitability, liquidity level, company size and asset structure on the capital structure of companies in the consumer goods industry sector, the food and beverage sub-sector, which are listed on the Indonesia Stock Exchange (IDX) for the 2018-2021 period. This research is Quantitative Research with Secondary Data. The sampling method is Purposive Sampling. The analysis technique uses multiple linear regression analysis with the help of SPSS version 23. Based on the results of the partial test research shows that profitability, company size and asset structure of each variable partially have no effect on capital structure, and the level of liquidity partially has a positive and significant effect on structure capital of companies in various industrial sectors